Davidsen-Nielsen, Niels: Tense and Mood in English. A Comparison with Danish. Mouton de Gruyter, Berlin/New York 1990. Topics in English Linguistics 1. x + 224 pp. - Lauridsen, Karen M. (HERMES - Journal of Language and Communication in Business, 1991)
No abstract.